Transient evoked otoacoustic emissions and auditory brainstem response in infants with perinatal asphyxia - Ribeiro, Georgea Espindola [UNESP]; Silva, Daniela Polo Camargo da [UNESP]; Montovani, Jair Cortez [UNESP] (Elsevier, 2016)
Objective The objective of this study was to verify the effects of perinatal asphyxia on different parts of the auditory system. Methods This was a non-concurrent cohort study conducted on a fixed population in a tertiary public hospital. Participants included 181 infants born at term who underwent the transient evoked otoacoustic emission test as a part of a neonatal hearing screening program, with a “pass” result in both ears, and by auditory brainstem response testing. The infants were divided into 3 groups: G1, 20 infants who had perinatal asphyxia; G2, 111 infants with an Apgar score lower than 4 in the first minute and/or lower than 6 in the fifth minute (called “low Apgar” at birth); and G3, 50 infants with first- and fifth-minute Apgar scores ≥7. Results The signal-to-noise ratio of transient evoked otoacoustic emissions were greater in G3 compared with G1 and G2 at 4 kHz frequency for males. An increased latency of waves I and III in the auditory brainstem response of male infants in G1 was observed. Conclusion This study demonstrated that alterations occurred in both the cochlear and the neural components in male infants who had perinatal asphyxia.
Keywords: Electrophysiology; Hearing loss; Neonatal screening; Newborn infant